A Low-energy High Managing Energy Use for Commercial Indoor Cannabis Cultivation. Issue 4 (1st April 2017) - Jonlin, Duane L.; Lewellen, Duane J.
ABSTRACT: With legalization in Washington, Colorado, Oregon and Alaska, and on the ballot in California and other states, illegal marijuana growing operations are gradually being replaced with taxed and licensed businesses. This provides for the first time an opportunity to manage the notoriously high energy use required for indoor cannabis production. In urban areas, these new commercial operations typically operate in secure warehouse facilities, some of them massive in scale. Lighting represents by far their largest energy use, with cooling and dehumidification also adding substantial loads, to create energy use intensities up to 20 times that of new office buildings. This year-round demand can also be 50 times that of the previous use of a warehouse, putting unplanned demands on the local utility infrastructure. However, lighting and HVAC (heating, ventilating, and air conditioning) systems capable of substantially reducing this energy use are available, with good financial returns in spite of their higher price tags. This article examines the costs, energy consumption and plant growth efficacies of the available lighting and HVAC options, and discusses the significant differences in the measurement of efficacy between horticultural lighting and vision lighting. Potential structures of utility incentive programs are discussed in light of the unique legal and financial constraints of this new industry.